The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1403129
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy and fluorescence for the detection of liver cancer and abnormal liver tissue

Abstract: In this paper, laser induced human serum Raman spectra of liver cancer are measured. The spectra in serum differences between normal people and liver cancer patients are analyzed. For the typical spectrum of normal serum, there are three sharp Raman peaks and relative intensity of Raman peaks excited by 514.5 nm is higher than that excited by 488.0 nm. However, for the Raman spectrum of liver cancer serum there are no peaks or very weak Raman peaks at the same positions. To liver cirrhosis, the shape of Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…A few reports have shown that the serum autofluorescence produced by native fluorescent substances in the blood may be used to diagnose liver cancer [ 10 12 ]. The laser-induced serum Raman spectra of patients with liver cancer differed from those of cirrhosis patients or normal subjects [ 11 ], and this difference was diagnostically significant for liver cancer [ 10 ]. However, the principle component of the spectra could not discriminate cirrhosis patients with and without HCC [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few reports have shown that the serum autofluorescence produced by native fluorescent substances in the blood may be used to diagnose liver cancer [ 10 12 ]. The laser-induced serum Raman spectra of patients with liver cancer differed from those of cirrhosis patients or normal subjects [ 11 ], and this difference was diagnostically significant for liver cancer [ 10 ]. However, the principle component of the spectra could not discriminate cirrhosis patients with and without HCC [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the sensitivity and/or specificity of a single biomarker for tumor diagnosis are invariably inadequate. Thus, the combination of several biomarkers for diagnosis is a reasonable strategy by which to address this problem [ 11 ]. Interestingly, the combination of conventional blood tests is useful for predicting [ 16 ] and diagnosing [ 17 ] HCC, especially when combined with AFP.…”
Section: Introductionmentioning
confidence: 99%
“…Sınıflandırıcı olarak DVM kullanarak bölgeleri hemanjiyom, hepatom veya siroz olarak sınıflandırmışlardır [8]. Daha bir çok uygulamada değişik tip görüntüleme teknikleri ve sınıflandırma yöntemleri kullanılarak karaciğer sirozu sınıflandırmaları yapılmıştır [9][10][11][12][13][14].…”
Section: Introductionunclassified